Security supervision and management : the theory and practice of asset protection - Davies, Sandi J.; Hertig, Christopher A.; Gilbride, Brion P. (Amsterdam ; Boston : Butterworth-Heinemann is an imprint of Elsevier, 2015)
Security Supervision and Management, Fourth Edition, fills the basic training needs for security professionals who want to move into supervisory or managerial positions. Covering everything needed from how to work with today's generation security force employees to the latest advances in the security industry, Security Supervision and Management, Fourth Edition, shows security officers how to become a more efficient and well-rounded security professional. Security Supervision and Management, Fourth Edition, is also the only text needed to prepare for the Certified in Security Supervision and Management (CSSM) designation offered by International Foundation for Protection Officers (IFPO).
Petersen's Accident/Incident ModelSystems Models; The Integration of Theories and General Safety Program Implications; Emerging Trends; End Notes; 6 -- An Introduction to the Supply Chain; What Is the Supply Chain?; Time and Cost versus Impacts; Information Is Everything; End Notes; Unit II -- Basics of Supervision; 7 -- Supervisory Characteristics and Expectations; Contract versus Proprietary; The Promotion to Supervisor; The Impact of Poor Supervision; What Employees Expect from Supervisors; Conclusions; End Notes; 8 -- Company Policy and Procedures: The Security Supervisor's Primer.
Includes bibliographical references and index.
Online resource; title from PDF title page (Ebsco, viewed June 18, 2015).
Elsevier
Keywords: Police, Private -- Training of -- Handbooks, manuals, etc; Police, Private -- Management -- Handbooks, manuals, etc; Private security services -- Handbooks, manuals, etc; Private security services -- Management -- Handbooks, manuals, etc; POLITICAL SCIENCE / Political Freedom & Security / Law Enforcement; Police, Private -- Management -- Handbooks, manuals, etc; Police, Private -- Training of -- Handbooks, manuals, etc; Private security services -- Handbooks, manuals, etc; Private security services -- Management -- Handbooks, manuals, etc; Police, Private -- Management; Police, Private -- Training of; Private security services; Private security services -- Management; Electronic books; Handbooks and manuals